What Shall We Think About an Afrocentric Vision? - Biernaczky, Szilárd (Afrika Tanulmányok / Hungarian Journal of African Studies, 2021)
This essay was originally a lecture given in Hungarian in Pécs, Hungary, at a conference on African Globalities/Global Africans, the 4th Pécs African Studies Conference on June 9-10, 2016. It starts its analysis with the ancient Greeks, since when, and even more so since Hegel, we have known that in the fields of both thinking and actions, along theses and antitheses, then with luck, along syntheses, “welter” the phrasing of notions and conceptions and the debates over them as well as everyday and historical events. We also know that syntheses many times are born with difficulty. What is more, in many cases, series of theses and antitheses get to grips with each other for a long period of time without the hope of creating a synthesis. And of course, to open the gates elsewhere: this old-world syllogism, as a reflective model, is not sufficient for the interpretation of the realistic and mental entity that inundates us. However, nowadays we can pick up on the specific mental-interpretational ideology that stands out in the form of this model whose essence is Afrocentrism set against the Eurocentric approach (Biernaczky, 2017). This is discussed in the paper.